Occurrence of Listeria spp. in seafood handling environments - Jeyasekaran, G; Karunasagar, Indrani; Karunasagar, I (Indian Journal of Fisheries, 2011)
The occurrence of Listeria spp. in seafood handling/ processing environments was studied. Environmental swab samples were collected from fishing vessel, fish landing centre and seafood processing plants located in Mangalore. Of the 119 environmental swab samples examined, 9 were positive for Listeria spp. particularly L. monocytogenes. L. welshmeri was also present in a sample. Three samples from boat deck and one from floor of fish landing centre yielded L. monocytogenes. Of the 5 samples from seafood processing plants that were positive for L. monocytogenes, two were from the plate freezer, two from worker’s hands and one from processing table. The results suggest that Listeria spp. in seafood handling/ processing environments may cross contaminate the seafoods that were initially free from this pathogen, which will lead to public health hazard on consumption of such contaminated foods. They may also have serious impact on the cleaning and sanitizing schedule of the seafood contact surfaces